Aluminum silicate fiber membrane: A cost-effective substitute for fiber glass separator in Li–O2 battery. (September 2020) - Zhao, Z.; Pan, L.; Li, Y.; Wang, J.; Luo, Z.; Chen, W.; Liu, Z.; He, H.
Abstract: Currently, glass fiber membrane is widely used as the separator in Li–O2 batteries due to its high ionic conductivity, electrolyte uptake and thermal stability. Unfortunately, its high cost hinders the future commercialization of Li–O2 battery. Herein, a cost-effective aluminum silicate fiber (ASF) membrane was utilized for the first time to replace the conventional glass fiber as the separator in Li–O2 batteries. Thanks to the high ionic conductivity and good electrolyte wettability, batteries with ASF separator exhibit high electrochemical performance, even better than those with commercial glass fiber. In addition, the ASF membrane also shows better thermal stability under extreme conditions. Impressively, the cost of aluminum silicate fiber is less than 1% of the glass fiber (2.3 /m 2 vs. 370.7 /m 2 ). The combination of excellent performance and low cost promises it to be an ideal substitute for the conventional glass fiber as the separator for Li–O2 batteries. Graphical abstract: Image 1 Highlights: A better wettability of aluminum silicate fiber separator (ASF) leads to higher ionic conductivity. High thermal stability offers excellent safety properties. The cost of ASF separator is 2.3 /m 2, less than 1% of the GF (367.2 /m 2 ), which is more competitive in metal air batteries.